Metabolic shift of the kynurenine pathway impairs alcohol and cocaine seeking and relapse - Vengeliene, Valentina; Spanagel, Rainer (Psychopharmacology, 2016)
Rationale: The glutamatergic system plays a key role in the maintenance of drug use and development of drug-related conditioned behaviours. In particular, hyper-glutamatergic activity and N-methyl-D-aspartate receptor (NMDAR) activation may drive drug craving and relapse. Inhibition of kynurenine-3-monooxygenase (KMO) shifts the metabolic kynurenine pathway towards production of kynurenic acid, which leads to a reduction of glutamatergic/NMDAR activity via different mechanisms. Objectives: In this study, we investigated whether drug-seeking and relapse behaviour could be modified by the metabolic shift of endogenous kynurenine pathway. Methods: An inhibitor of kynurenine-3-monooxygenase (KMO) Ro61-8048 (4 and 40 mg/kg) and its prodrug JM6 (100 and 200 mg/kg) were tested in two behavioural rat models for drug seeking and relapse—the alcohol deprivation effect (ADE) model in long-term alcohol-drinking rats and the model of cue-induced reinstatement of alcohol- and cocaine-seeking behaviour. Results: Our results show that relapse-like alcohol drinking during the ADE was abolished by repeated intraperitoneal administration of Ro61-8048 and significantly reduced by its oral prodrug JM6. Cue-induced reinstatement of both alcohol- and cocaine-seeking behaviour was also abolished by administration of Ro61-8048. Conclusions: Pharmacological enhancement of endogenous kynurenic acid levels provides a novel treatment strategy to interfere with glutamatergic/NMDAR activity as well as with craving and relapse in alcohol-dependent patients and drug addicts.
Gesehen am 21.01.2019